Rabies vaccination in dogs in Laos: Owner knowledge and serological status of dogs - Velander, L.; Fogelberg, J.; Putthana, V.; Keosengthong, A.; Lindahl, Johanna F. (MDPI, 2022)
Rabies is an infectious disease which is virtually 100% fatal. Humans are most often infected through the bite of an infected dog, and most cases could be prevented by vaccinating dogs. However, vaccination coverage is insufficient in most countries where canine rabies occurs endemically. This study conducted interviews and sampling of dogs in Laos to understand more about the barriers for vaccination and to evaluate the antibody status of dogs using a commercial ELISA. The study found that only 62% out of 359 dog owners knew what rabies was, and only 24% knew the disease could be fatal. Higher education was associated with higher knowledge scores. Only 56 out of 437 (13%) dogs had been rabies vaccinated according to their owner, and out of these dogs, only 34 (61%) had antibodies, and only 48% had adequate levels (above 0.5 IU/mL). However, 24% of the dogs with no known history of vaccination had antibodies, indicating either exposure or vaccination in the past without the owner’s awareness. In conclusion, this study indicates that there is a low level of knowledge about rabies, and that owner knowledge is not a good indicator of whether a dog is vaccinated or not.